2004
DOI: 10.1158/1078-0432.ccr-04-0048
|View full text |Cite
|
Sign up to set email alerts
|

Gene-Expression Profile Changes Correlated with Tumor Progression and Lymph Node Metastasis in Esophageal Cancer

Abstract: Purpose: The purpose of this research was to identify molecular clues to tumor progression and lymph node metastasis in esophageal cancer and to test their value as predictive markers.Experimental Design: We explored the gene expression profiles in cDNA array data of a 36-tissue training set of esophageal squamous cell carcinoma (ESCC) by using generalized linear model-based regression analysis and a feature subset selection algorithm. By applying the identified optimal feature sets (predictive gene sets), we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
69
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(72 citation statements)
references
References 39 publications
3
69
0
Order By: Relevance
“…and abbreviations were obtained from the URL website (http://www.ncbi.nih.gov/entrez/query.fcgi?db=gene). (18). Thus, in conjunction with our present finding, we propose that predictors for LN metastasis in ESCC should be established separately according to tumor invasion depth (pT1 and pT2-4) to obtain high predictive ability in a large cohort.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…and abbreviations were obtained from the URL website (http://www.ncbi.nih.gov/entrez/query.fcgi?db=gene). (18). Thus, in conjunction with our present finding, we propose that predictors for LN metastasis in ESCC should be established separately according to tumor invasion depth (pT1 and pT2-4) to obtain high predictive ability in a large cohort.…”
Section: Discussionsupporting
confidence: 76%
“…With respect to ESCC, there have been many DNA microarray studies identifying genes related to pathogenesis or therapy of ESCC (8)(9)(10)(11)(12)(13)(14)(15)(16); however, only two studies considered and analyzed LN metastasis (17,18). Kan et al (17) reported that molecular profiling of 60 genes accurately predicted LN metastasis in 10 of 13 (77%) ESCCs.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Gene expression profiling studies have been used in the examination of cancer progression, diagnosis, drug target discovery, and gene therapy evaluation (Brabender et al, 2004;Chang et al, 2004;Tamoto et al, 2004). Our previous cDNA microarray-based expression profiling studies global genetic signatures in esophageal cancer Xu et al, 2002).…”
Section: Introductionmentioning
confidence: 99%